2020
DOI: 10.21203/rs.3.rs-19104/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Twelve-Month Prevalence of Psychiatric Morbidity in Cancer Patients in a Nigerian Oncology Centre

Abstract: Background Cancer is a leading cause of mortality worldwide and is associated with a wide range of psychiatric morbidity.Methods In this descriptive study, 130 patients with different types of cancer were interviewed. Information on sociodemographic characteristics, medical comorbidity, stage of cancer, duration of treatment was obtained. Psychological distress was assessed using the GHQ-12, and psychosocial distress with the Distress Thermometer (DT). The MINI was used to establish the presence or absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…There were 19 studies on psychiatric disorders among adult patients with cancer in SSA. All the studies in this category were consistent in reporting a high prevalence of psychiatric disorders or its symptoms among the study participants 34,36,68–71 . The prevalence of any DSM‐IV disorder among adult patients with cancer was 66.9% 68 .…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…There were 19 studies on psychiatric disorders among adult patients with cancer in SSA. All the studies in this category were consistent in reporting a high prevalence of psychiatric disorders or its symptoms among the study participants 34,36,68–71 . The prevalence of any DSM‐IV disorder among adult patients with cancer was 66.9% 68 .…”
Section: Resultsmentioning
confidence: 61%
“…Higher rates of these disorders were reported using screening instruments such as the Patient Health Questionnaire‐9 (PHQ‐9), the Hospital Anxiety and Depression Scale (HAD‐S) and the Center for Epidemiologic Studies Depression Scale (Revised) (CES‐DR) 36,69,76,77 . Other psychiatric disorders reported included: opioid use disorder (26.9%), dysthymia (14.5%), post‐traumatic stress disorder (13.0%), psychosis (0.7%) and adjustment disorders 46,68 . One comparative study showed that people with cancer had significantly higher rates of major depressive disorder when compared to healthy control group (27.5% vs. 9.5%) 78 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations